Age-Dependent Changes in Sirolimus Metabolite Formation in Patients With Neurofibromatosis Type 1. Issue 3 (June 2015) - Emoto, Chie; Fukuda, Tsuyoshi; Mizuno, Tomoyuki; Cox, Shareen; Schniedewind, Björn; Christians, Uwe; Widemann, Brigitte C.; Fisher, Michael J.; Weiss, Brian; Perentesis, John; Vinks, Alexander A.
Abstract : Background: Sirolimus is an inhibitor of mammalian target of rapamycin, which exhibits large interindividual pharmacokinetic variability. We report sirolimus pharmacokinetic data collected as part of a concentration-controlled multicenter phase II clinical trial in pediatric patients with neurofibromatosis type 1. The purpose of this study was to explore the effect of growth on age-dependent changes in sirolimus clearance with a focus on cytochrome P450 3A (CYP3A) subfamily mediated metabolism. Methods: Predose blood samples were obtained at steady state from 18 patients with neurofibromatosis type 1. Sirolimus and its 5 CYP3A-dependent primary metabolites were quantified by HPLC–UV/MS. Concentration ratios of metabolites to sirolimus (metabolic ratio) were calculated as an index of metabolite formation. Results: Metabolic ratios of the main metabolites, 16- O -demethylsirolimus (16-O-DM) and 24-hydroxysirolimus (24OH), were significantly correlated with sirolimus clearance, whereas this was not the case for the other 3 metabolites (25-hydroxysirolimus, 46-hydroxysirolimus, and 39- O -demethylsirolimus). The ratios for the 16-O-DM and 24OH metabolites were lower in children than adults. No significant difference in allometrically scaled metabolic ratios of 16-O-DM and 24OH was observed between children and adults. Conclusions: This study suggests that the age-dependent changes in sirolimus clearance can be explained by size-related increases in CYP3A metabolic capacity, most likely due to liver and intestinal growth. These findings will help facilitate the development of age-appropriate dosing algorithms for sirolimus in infants and children.